REWARD SYSTEM FOR ACHIEVING MARKETING TARGETS IN MOTOR FINANCING SCHEME OF FIF BANDA ACEH ACCORDING TO ISLAMIC ECONOMIC LAW - Aksar, Muhammad Azrial; Muhammad Iqbal (JURISTA: Jurnal Hukum dan Keadilan, 2024)
The Federal International Finance (Hence called PT.FIF) branch Banda Aceh city is a financing institution that facilitates the people to financing of their needs. This company collaborates with reseller shops and distributors, allowing customers to buy goods using an installment system. Partner stores act as facilitators between PT FIF and customers, helping to market financing products. This research examines the rewards or commissions given by PT FIF to partner stores based on their marketing performance, with a focus on whether they are in line with the ji'alah agreement (marketing achievement commission) from the Islamic Economic Law perspective. Using a normative-sociological approach and descriptive-analytical methods, this research aims to analyze the concept and practice of the ji'alah agreement in sharia financing marketing partnerships. The research results show that the practice of giving commissions by PT FIF to partner shops is generally in line with the principle of the ji'alah agreement. However, several aspects were found that needed adjustment to be more in line with sharia provisions, such as clarity in determining the commission amount and target achievement period. Research also reveals that partner shops' understanding of the ji'alah concept is still limited, so further education is needed to increase awareness of the sharia aspects of this partnership.